Piping and pipeline calculations manual : construction, design, fabrication, and examination - Ellenberger, J. Phillip (Butterworth-Heinemann/Elsevier, 2010)
The integrity of a piping system depends on the considerations and principles used in design, construction, and maintenance of the system. Piping systems are made of many components such as pipes, flanges, supports, gaskets, bolts, valves, strainers, flexibles, and expansion joints. These components can be made in a variety of materials, in different types and sizes, and may be manufactured to common national standards or according a manufacturers proprietary item. This book provides engineers and designers with a?quick reference guide? to the calculations, codes, and standards. The lack of commentary, or historical perspective, regarding the codes and standards requirements for piping design and construction is an obstacle to the designer, manufacturer, fabricator, supplier, erector, examiner, inspector, and owner who want to provide a safe and economical piping system. An intensive manual, this book will utilize hundreds of calculation and examples based on of 40 years of personal experiences of the author as both an engineer and instructor. Each example demonstrates how the code and standard has been correctly and incorrectly applied. This book is a?no nonsense? guide to the principle intentions of the codes or standards and provides advice on compliance. After using this book the reader should come away with a clear understanding of how piping systems fail and what the code requires the designer, manufacturer, fabricator, supplier, erector, examiner, inspector, and owner to do to prevent such failures. The focus of the book is to enhance participants? understanding and application of the spirit of the code or standard and form a plan for compliance. The book is enhanced by a multitude of calculations to assist in problem solving, directly applying the rules and equations for specific design and operating conditions to illustrate correct applications. Each calculation is based on a specific code. The major codes covered in the book are: American Society of Mechanical Engineers?B31.3 - 2002 - Process Piping?B31.8 - 2003 - Gas Transmission and Distribution Piping Systems?B31.8S - 2001 - 2002 - Managing System Integrity of Gas Pipelines?B31.4 - 2002 - Pipeline Transportation Systems for Liquid Hydrocarbons and Other Liquids?B16.34 - 2004 Valves Flanged, Threaded and Welding End American Petroleum Institute?API SPEC 6D - Specification for Pipeline Valves.?API 526 - Flanged Steel Pressure Relief Valves.?API 527 - Seat Tightness of Pressure Relief Valves R(2002).?ANSI/API STD 594 - Check Valves: Flanged, Lug, Wafer and Butt-welding.?API 598 - Valve Inspection and Testing. The book covers American Water Works Association standards where they are applicable. Utilizes hundreds of calculation and examples Guide to the principle intentions of the codes Easy to follow advice on code compliance Directly applies equations for specific design.